2020
DOI: 10.3389/fmars.2020.578595
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Surface Orientation in Biodiversity Monitoring Protocols: The Case of Patagonian Rocky Reefs

Abstract: Temperate rocky reefs in Atlantic Patagonia are productive areas that support a high diversity of invertebrates, algae, and fishes. Complex surface structures on rocky reefs offer a range of microhabitats, which in turn, lead to a broad variety of co-existing species. Despite their ecological importance and the ecosystem services they provide, Patagonian rocky reef habitats have received limited attention. Until now studies have not discerned nor consequently described the assemblages found on each of the diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Most of the available information about Atlantic Patagonian marine biodiversity is related to rocky intertidal communities or rocky reef fish communities. Despite having more than 4000 km of coastline, in the last 20 years only four studies have focused on subtidal benthic communities from shallow rocky reefs in Argentina ( Genzano et al 2011 , Rechimont et al 2013 , Bravo et al 2015 , Bravo et al 2020a ). However, none of them described the epi-benthic community of different surface orientations on the rocky reefs.…”
Section: New Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the available information about Atlantic Patagonian marine biodiversity is related to rocky intertidal communities or rocky reef fish communities. Despite having more than 4000 km of coastline, in the last 20 years only four studies have focused on subtidal benthic communities from shallow rocky reefs in Argentina ( Genzano et al 2011 , Rechimont et al 2013 , Bravo et al 2015 , Bravo et al 2020a ). However, none of them described the epi-benthic community of different surface orientations on the rocky reefs.…”
Section: New Informationmentioning
confidence: 99%
“…They create a unique habitat that is distinguished from rocky flat or soft bottoms because of the presence of outcrops with crevices and small caves that provide refuges for fish species that are only found in these systems ( Galván et al 2009 ). As such, rocky reefs provide important marine ecosystem services for recreational fishing, scuba diving activities and have educational and scientific research value ( Bravo et al 2015 , Bravo et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…More particularly, the terrain complexity (e.g. rugosity, bathymetric variance and slope of the slope), its morphology (curvature and aspect), the substrate type (nature, features and engineer species) and other information (bathymetry and slope) have an influence on the presence, abundance, cover and diversity of algae and sessile invertebrates both in tropical (Duckworth, 2016), subtropical (Holmes et al, 2008;Zavalas et al, 2014, Bravo et al, 2020 and temperate environments (Castric-Fey et al, 1973, Castric-Fey andChasse, 1991;Guinan et al, 2009;Elvenes et al, 2014). Studies have demonstrated that the terrain complexity is one of the key-factor strongly structurating the fish communities on tropical (Kuffner et al, 2007;Pittman et al, 2007;Pittman et al, 2009;Knudby et al, 2010;Pittman and Brown, 2011;Sekund and Pittman, 2017), subtropical (Moore et al, 2009;Monk et al, 2010;Moore et al, 2010;Monk et al, 2011;Coleman et al, 2016;Rees et al, 2018;Williams et al, 2019), and temperate reefs (Cameron et al, 2014).…”
Section: Introductionmentioning
confidence: 99%